Go-Pest Technology for Sustainable Agriculture and Economic Efficiency - Dewa Nyoman Wahyu Ariana; Ni Putu Dian Rahayu Ningsih; Ni Putu Indri Suartini; Ketut Linda Aryani; Wayan Wira Adnyana; Made Ayu Swari Oktarini; Ni Luh Ayu Yuliantari (IAIN Madura, 2026)
This study aims to examine the innovation of Go-Pest technology as an eco-friendly solution to improve economic efficiency in the agricultural sector and to support Education for Sustainable Development (ESD). The main problem addressed is the high dependence of farmers on chemical pesticides, which contribute to environmental degradation, increased production costs, and potential health risks. This research employs a descriptive qualitative approach through literature review and conceptual analysis to explore the relationship between technological innovation, economic efficiency, and sustainability. The findings indicate that Go-Pest technology, which utilizes infrasonic waves combined with a digital monitoring system, is effective in reducing pest disturbances without causing environmental harm. Furthermore, the implementation of this technology contributes to economic efficiency by reducing pesticide costs, minimizing labor requirements, and increasing agricultural productivity. From an ESD perspective, this innovation integrates environmental, economic, and technological aspects to support sustainable agricultural practices. Therefore, Go-Pest technology has significant potential as an innovative solution to promote sustainable agriculture while improving farmers’ welfare.